Daya Saing Kultural dan Pemenuhan Kebutuhan Pasar Tenaga Kerja Berdasar Siklus Waktu Dengan Supply Chain - Damayanti, Damayanti (potensio, 2008)
Supply chain really necessary for organization to pass on valueadded to consumer via optimalisasi time, allocating, and productamount flow fast one and on the nose. With supply chain, culturalcompetitiveness is engaged based order accomplishment cycletime, which is durasi time to pass on customer requisition to goodsor service product, in this case is accomplish to see dammed hellfirst firm will grad of college. With supply chain, culturalcompetitiveness that covers: entrepreneurship, innovativeness, andlearning, can to order fulfillment labor market based on cycle time;and is the cultural competitiveness negatively related to orderfulfillment labor market based on cycle time.Keyword : supply chain, cultural competitiveness, fulfillment labormarket based on cycle time